Fools Rush in? The Institutional Context of Industry Creation - Aldrich, Howard E.; Fiol, C. Marlene (Academy of Management Review, 1994)
New organizations are always vulnerable to the liabilities of newness, but such pressures are especially severe when an industry is in its formative years. We focus on one set of constraints facing entrepreneurs in emerging industries ? their relative lack of cognitive and sociopolitical legitimacy. We examine the strategies that founders can pursue, suggesting how their successful pursuit of legitimacy may evolve from innovative ventures to broader contexts, collectively reshaping industry and institutional environments.